An Adaptive Photovoltaic Topology to Overcome Shading Effect in PV Systems - Mohamed Amer Chaaban; Lana El Chaar; Mahmoud Alahmad (International Journal of Photoenergy)
Shading in photovoltaic systems can cause many undesired effects. When shading occurs, the power generated from the PV system is much less than nominal power, increasing the electrical mismatching losses between PV system components. Active research to address this power loss focuses on static and adaptive systems. This paper addresses an adaptive system solution and proposes a new method to adaptively overcome losses due to shading during low radiation conditions. In addition, a statistical analysis for choosing the most feasible and efficient configuration for the system size is presented. The proposed system has been validated under shade conditions in a simulation and prototype experiment. The experiments are conducted using a PV system consisting of 10 PV modules located at the Petroleum Institute in the United Arab Emirates. The proposed system is shown to minimize the shading losses of the PV array in real time by an average of 100% under simulated conditions and 84% in practical experiments.